2011
DOI: 10.1097/ccm.0b013e3181feb8f6
|View full text |Cite
|
Sign up to set email alerts
|

Partial do-not-resuscitate orders: A hazard to patient safety and clinical outcomes?*

Abstract: Discouraging partial do-not-resuscitate(s) order may help promote more accurate and comprehensive advance care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…However, in line with previous studies, some nurses also mentioned the possibility that the patient could receive reduced care in the case of a DNR decision. 17,47 Several of the interviewed nurses mentioned the importance of treating the patient at the end of life with dignity, and they weighed this value against the risk of not having a dignified life after resuscitation. Obstacles to good nursing care mentioned were no clear decision on DNR and inadequate reporting and documentation which could cause unintended CPR.Other studies have shown that a dignified death for the patient is an important value for nurses 18 and that nurses strive to create a peaceful death where family members are allowed to participate.…”
Section: Discussionmentioning
confidence: 99%
“…However, in line with previous studies, some nurses also mentioned the possibility that the patient could receive reduced care in the case of a DNR decision. 17,47 Several of the interviewed nurses mentioned the importance of treating the patient at the end of life with dignity, and they weighed this value against the risk of not having a dignified life after resuscitation. Obstacles to good nursing care mentioned were no clear decision on DNR and inadequate reporting and documentation which could cause unintended CPR.Other studies have shown that a dignified death for the patient is an important value for nurses 18 and that nurses strive to create a peaceful death where family members are allowed to participate.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of our patient population was limited. Future studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) should assess potential associations between code status and preference discrepancies and race/ethnicity. Previous investigators' work suggests that patient preferences depend heavily on how scenarios are described to patients.…”
Section: Dnr/dni Patient Preferencesmentioning
confidence: 99%
“…Some have noted that unbridled commitment to autonomy has led to the development of partial DNR orders, which frequently express preferences for illadvised or even incoherent constellations of treatments, such as the use of intravenous medications without chest compressions in the case of cardiac arrest. 22,27 We interpreted a DNR order as expressing a patient's preference to forgo CPR in the case of cardiac arrest and a DNI order as indicating a preference to forgo intubation even when indicated. Several investigations have noted substantial variation in how clinicians interpret DNR/DNI orders.…”
Section: Dnr/dni Patient Preferencesmentioning
confidence: 99%
“…Some organizations and clinicians have navigated these questions by implementing "partial" code orders, although these are controversial. 17,18 Similar to IMV, ECMO can be a component of CPR but can also be indicated in other contexts. Thus, ECMO would likely be subject to similar questions: Should a DNR order be interpreted as implying a DNE order and, if so, in what clinical circumstances?…”
mentioning
confidence: 99%